William Francis Bernard Simmons correspondence - Simmons, William Francis Bernard, 1884-1949.
Fourteen ALsS written by Simmons to Roy Baker Harris relating to the creation of bookplates and other art projects.
Artist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Harrus, Roy Baker -- Correspondence; Art, American; Bookplates, American; Artists